(60-k)-6=5(k-6)

Subtract 6 from 60.

-k+54=5(k-6)

Apply the distributive property.

-k+54=5k+5⋅-6

Multiply 5 by -6.

-k+54=5k-30

-k+54=5k-30

Subtract 5k from both sides of the equation.

-k+54-5k=-30

Subtract 5k from -k.

-6k+54=-30

-6k+54=-30

Subtract 54 from both sides of the equation.

-6k=-30-54

Subtract 54 from -30.

-6k=-84

-6k=-84

Divide each term in -6k=-84 by -6.

-6k-6=-84-6

Cancel the common factor of -6.

Cancel the common factor.

-6k-6=-84-6

Divide k by 1.

k=-84-6

k=-84-6

Divide -84 by -6.

k=14

k=14

Solve for k (60-k)-6=5(k-6)